AN EPISTMOLOGICAL REVIEW ON HUMANISTIC EDUCATION THEORY - Lilik Untari (UIN Raden Mas Said Surakarta, 2016)
Humanism as a paradigm is often declared as an alternative approach to education. This paradigm is, in fact, an approach developed in the field of literature and education. The objective of this study is to determine the values underlie the epistemology of the humanistic education theory. Epistemology is the elements that are abstract or implicit. To recognize the epistemology of humanism education theory, this study examines the elements of basic assumptions, values and models of the theory. The results show that the assumptions promoting the theory have similarities with the basic assumptions of the phenomenological epistemology. It sees humans as creatures with consciousness and knowledge for what he did. Thus, every human’s behavior or action is conducted in purpose. In humanistic education theory, meaningfulness and usefulness of the learning process are determined by the learner, not the educator. For that reason, learning design and methods should be developed by the participants based on the needs of the learners. Therefore, the theory does not provide a model for an individual learning process. Thus, it can be concluded that the theory of humanism education rooted from phenomenology epistemology.